The debacle - Zola, Emile (b, 1972)
Conservative and working-class, Jean Macquart is an experienced, middle-aged soldier in the French army, who has endured deep personal loss. When he first meets the wealthy and mercurial Maurice Levasseur, who never seems to have suffered, his hatred is immediate
Keywords: Franco-Prussian War. -- Fiction